TRANSAKSI LIKUIDITAS DI LEMBAGA KEUANGAN MIKRO SYARIAH DITINJAU DARI HUKUM EKONOMI ISLAM - Suhatri Mariko (IAIN Batusangkar, 2015)
This qualitative research was aimed at describing the implementation Qardh and Wadiah Yad Dhamanah in the transaction of liquidity which was done by KJKS- BMT in Tanah Datar and the perpective of Islamic Economy Law toward the implementation of this transaction. The results revealed that the implementation of transaction liquidity (KJKS-BMT) in Tanah Datar Regency was conducted in two kinds of transactions Wadi’ah Yad Dhamanah and Qardh. According to Islamic Economy Law Wadi’ah Yad Dhamanah was accepted and Qardh was forbidden.Keywords: Transaction of Liquidity, Micro Syari’ah Financial Institution, Economy Syari’ah